Simplifying 3a + -2b = 5a + 6b Solving 3a + -2b = 5a + 6b Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-5a' to each side of the equation. 3a + -5a + -2b = 5a + -5a + 6b Combine like terms: 3a + -5a = -2a -2a + -2b = 5a + -5a + 6b Combine like terms: 5a + -5a = 0 -2a + -2b = 0 + 6b -2a + -2b = 6b Add '2b' to each side of the equation. -2a + -2b + 2b = 6b + 2b Combine like terms: -2b + 2b = 0 -2a + 0 = 6b + 2b -2a = 6b + 2b Combine like terms: 6b + 2b = 8b -2a = 8b Divide each side by '-2'. a = -4b Simplifying a = -4b